Heating up the OER: Investigation of IrO2 OER Catalysts as Function of Potential and Temperature. Issue 19 (19th September 2022) - Czioska, Steffen; Ehelebe, Konrad; Geppert, Janis; Escalera‐López, Daniel; Boubnov, Alexey; Saraçi, Erisa; Mayerhöfer, Britta; Krewer, Ulrike; Cherevko, Serhiy; Grunwaldt, Jan‐Dierk
Abstract: Despite intensive investigations for unravelling the water splitting reaction, the catalyst behavior during the oxygen evolution reaction (OER) is still not fully understood. This is especially true under more demanding conditions like high potentials and high temperatures. Rotating disk electrode measurements show a gradual increase of OER current when increasing the temperature up to 80 °C. However, strong bubble formation at elevated temperatures makes in‐situ characterization of the catalyst challenging. Here we utilize an in‐situ electrochemical and heated flow cell, which aims at an efficient removal of bubbles from the catalyst surface and enables structural studies by X‐ray absorption spectroscopy (XAS) at temperatures up to 80 °C. Changes in the Ir L3 ‐edge X‐ray absorption near edge spectra (XANES) were observed with respect to the white line position and principal components related to structural changes were extracted. At temperatures of 60 °C and above, the white line position of XANES spectra reaches a steady state, which is possibly caused by an equilibrium of different Ir oxidation states. These findings provide first spectroscopic insights in the behavior of OER catalysts at elevated temperatures which are typical for industrial applications and rarely addressed until now. Abstract : Heating up the OER : IrO2 is investigated at elevated temperature and high overpotentials for the oxygen evolution reaction. The presented approach enables these measurements at conventional XAS beamlines and shows that for a full and application relevant understanding the catalyst behavior under elevated temperatures have to be considered.